2014
DOI: 10.1016/j.nmd.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Atypical phenotype in two patients with LAMA2 mutations

Abstract: Congenital muscular dystrophy type 1A is caused by mutations in the LAMA2 gene, which encodes the a2-chain of laminin. We report two patients with partial laminin-a2 deficiency and atypical phenotypes, one with almost exclusive central nervous system involvement (cognitive impairment and refractory epilepsy) and the second with marked cardiac dysfunction, rigid spine syndrome and limb-girdle weakness. Patients underwent clinical, histopathological, imaging and genetic studies. Both cases have two heterozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…In 2010, Germanyeh et al [11] reported 5 patients with absent laminin α2 staining and cardiac abnormalities including mitral regurgitation, pulmonary hypertension, palpitations and wall motion hypokinesia on echocardiogram (Table 2). More recently, 3 patients (Table 2) have been described with cardiopathy: 2 with dilated cardiomyopathy, one of whom with ventricular arrhythmia [9] and one with impaired left ventricular contractility [34]. All of these reports combined with our patients (Patients #1 and #3) suggest that laminin α2 deficiency may indeed lead to an overt cardiomyopathy.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In 2010, Germanyeh et al [11] reported 5 patients with absent laminin α2 staining and cardiac abnormalities including mitral regurgitation, pulmonary hypertension, palpitations and wall motion hypokinesia on echocardiogram (Table 2). More recently, 3 patients (Table 2) have been described with cardiopathy: 2 with dilated cardiomyopathy, one of whom with ventricular arrhythmia [9] and one with impaired left ventricular contractility [34]. All of these reports combined with our patients (Patients #1 and #3) suggest that laminin α2 deficiency may indeed lead to an overt cardiomyopathy.…”
Section: Discussionmentioning
confidence: 59%
“…A smaller transcript arising from skipping of the exon containing the mutation and retaining the open reading frame was detected, thereby sustaining the presence of a partially functional laminin α2 chain. The other missense mutation identified in patients #3 and #4 (c.2461A>C, p.Thr821Pro) was already reported, associated with a missense variation (c.812C>T, p.Thr271Ile) at compound heterozygous state [34]. The patient had an exclusive central nervous system involvement showing among other things, refractory epilepsy associated with progressive cognitive regression since the age of 6, area of agyria in the occipital cortex on brain MRI, extensive white matter abnormalities with swelling and resulting widening of gyri.…”
Section: Discussionmentioning
confidence: 99%
“…Panel A: Map of missense single amino acid substitutions and in-frame deletions causing a muscular dystrophy with absent, reduced or normal expression of laminin-a2. Mutations causing absence (blue (black in print versions) text, colored online) or either reduced or normal (red (light gray in print versions), orange italics (light gray in print versions), colored online) laminin-a2 expression based on biopsy immunostaining are distinguished for the indicated mutations (Leiden Open Variation Database, www.dmd.nl/LAMA2_seqvar.html;Chan et al, 2014;Di Blasi et al, 2005;Gavassini et al, 2011;Geranmayeh et al, 2010;Marques et al, 2014;Oliveira et al, 2008;Rajakulendran, Parton, Holton, & Hanna, 2011). Panel B: Lma5eLNeLEa domains.…”
Section: Laminin-deficient Muscular Dystrophy and Neuropathymentioning
confidence: 99%
“…In late-onset phenotypes the onset age can range from early childhood to adult, and the patients could walk around independently compared to most earlyonset patients gaining no ambulation all their life. A patient even had no manifestation or physical sign relevant to muscles but the problems in central nervous system were remarkable [15]. Interestingly, the brain MRI showed white matter abnormalities regardless of their muscle severity [16].…”
Section: Discussionmentioning
confidence: 99%